In vitro activities of 11 fluoroquinolones against 816 non-typhoidal strains of Salmonella enterica isolated from Finnish patients with special reference to reduced ciprofloxacin susceptibility - Siitonen Anja; Pitkänen Susa; Kotilainen Pirkko; Huovinen Pentti; Hakanen Antti J (BMC, 2005)
Abstract Background The number of Salmonella strains with reduced susceptibility to fluoroquinolones has increased during recent years in many countries, threatening the value of this antimicrobial group in the treatment of severe salmonella infections. Methods We analyzed the in vitro activities of ciprofloxacin and 10 additional fluoroquinolones against 816 Salmonella strains collected from Finnish patients between 1995 and 2003. Special attention was focused on the efficacy of newer fluoroquinolones against the Salmonella strains with reduced ciprofloxacin susceptibility. Results The isolates represented 119 different serotypes. Of all 816 Salmonella strains, 3 (0.4%) were resistant to ciprofloxacin (MIC ≥ 4 μg/ml), 232 (28.4%) showed reduced susceptibility to ciprofloxacin (MIC ≥ 0.125 - 2 μg/ml), and 581 (71.2%) were ciprofloxacin-susceptible. The MIC50 and MIC90 values of ciprofloxacin for these strains were 0.032 and 0.25 μg/ml, respectively, being lower than those of the other fluoroquinolone compounds presently on market in Finland (ofloxacin, norfloxacin, levofloxacin, and moxifloxacin). For two newer quinolones, clinafloxacin and sitafloxacin, the MIC50 and MIC90 values were lowest, both 0.016 and 0.064 μg/ml, respectively. Moreover, clinafloxacin and sitafloxacin exhibited the lowest MIC50 and MIC90 values, 0.064 and 0.125 μg/ml, against the 235 Salmonella strains with reduced susceptibility and strains fully resistant to ciprofloxacin. Conclusion Among the registered fluoroquinolones in Finland, ciprofloxacin still appears to be the most effective drug for the treatment salmonella infections. Among the newer preparations, both clinafloxacin and sitafloxacin are promising based on in vitro studies, especially for strains showing reduced ciprofloxacin susceptibility. Their efficacy, however, has not been demonstrated in clinical investigations.